Pro Apache Struts with Ajax - Carnell, John. (The expert's voice in Java technology)
Pro Apache Struts with Ajax maps out how to use the Apache Struts MVC web framework, so you can solve everyday web application development challenges. This book takes an application-centric approach: the development of an application drives Struts along with Ajax coverage — not the other way around. Improper design can lead to long-term dependencies on the Struts framework, which makes code reuse difficult to achieve. This is the only book of its kind, covering the Struts 1.2 framework. It also covers evolutions into Shale and lightweight WebWork/Struts Ti. Authors John Carnell and Rob Harrop discuss Struts from an antipattern perspective, and the end result is that you'll learn to use Struts very effectively! What we do wrong: web antipatterns explained -- Struts fundamentals -- Form presentation and validation with Struts -- Managing business logic with Struts -- Architecting the data access tier with object relational bridge -- Building flexible front-ends with the tiles framework -- Dynamic forms and the Struts validator framework -- Speeding Struts development with XDoclet -- Logging and debugging -- Velocity template engine -- Extending the Struts framework -- Struts and Ajax.